The impact of intellectual property types on the performance of business start-ups in the United States. (June 2021) - Power, Bernadette; Reid, Gavin C
Using a large, longitudinal panel of US start-ups collected between 2004 and 2011, this article shows the extent to which intellectual property (IP) types, for example trademarks, patents, copyrights and outward licensing, enhance multidimensional performance. An ordered probit analysis corrected for sample selection bias, estimates performance to derive the following conclusions. First, trademarks and out-licensing IP types increase a firm's chances of being a high performer, confirming the importance of certain forms of IP protection for start-ups. Second, patenting significantly reduces the chances of being a high performer, suggesting patenting has limited performance benefits for start-ups. Third, few performance synergies exist in the joint use of IP types, suggesting that strong complementarities among IP types are limited. While out-licensing patents and out-licensing copyrights increase performance, out-licensing patents and out-licensing trademarks diminish it. Furthermore, registering more trademarks and out-licensing more trademarks also diminishes performance, suggesting start-up firms should keep trademarks in-house.